The expression of RoTat 1.2 variable surface glycoprotein (VSG) in Trypanosoma evansi and T. equiperdum - Claes, F.; Verloo, D.; Waal, D.T. de; Majiwa, Phelix A.O.; Baltz, T.; Goddeeris, Bruno M.; Büscher, Philippe (Elsevier, 2003)
In order to define whether the variable antigenic type RoTat 1.2 is restricted to Trypansoma evansi and could be used as antigen in serological tests to differentiate T. evansi from Trypansoma equiperdum, the appearance of RoTat 1.2-specific antibodies in rabbits, experimentally infected with T. evansi and T. equiperdum, respectively, was analyzed. Ten strains of T. evansi and 11 strains of T. equiperdum originating from Asia, Europe, Africa and Latin America were tested. Rabbit pre-infection sera and sera of days 7, 14, 25, 35 post-infection (p.i.) were analyzed for the presence of antibodies reactive with RoTat 1.2 in immune trypanolysis, ELISA/T. evansi and CATT/T. evansi. Within the duration of the infection (maximum 35 days), all T. evansi as well as 9 out of 11 T. equiperdum infected rabbits became positive in all these tests. The rabbits infected with T. equiperdum OVI and BoTat 1.1 (Morocco) remained negative in the immune trypanolysis test although the latter rabbit became positive in the CATT/T. evansi and ELISA/T. evansi. On the contrary, both rabbits were positive in immune trypanolysis when tested against their respective infecting population.From these data, we conclude that most T. equiperdum strains express isoVATs of RoTat 1.2. This explains, in part, why antibody tests based on T. evansi RoTat 1.2 cannot reliably distinguish between infections caused by T. evansi and those caused by T. equiperdum unless it can be proven that most described T. equiperdum are actually misclassified T. evansi.